P101 DOT1L inhibition increases dermal fibroblast proliferation but has no effects on in vitro or in vivo collagen deposition in models of fibrosis. (21st February 2018) - Berghen, N; De Langhe, E; Lories, R
Abstract : Introduction: Fibrosis is a key process in Systemic Sclerosis, a devastating disease that is not well understood. The role of epigenetic disease mechanisms is increasingly explored. DOT1L, the unique H3K79-methyltransferase, methylates histone 3 at the Lysine residue at position 79, and regulates gene expression. Inhibition of DOT1L has cell-type specific effects on Wnt-signalling, a pathway suggested to play an important role in fibrosis. Objectives: To study the role of DOT1L in fibrosis. Methods: Primary cell cultures of fibroblasts, isolated from healthy human skin and treated with DOT1L-inhibitor EPZ-5676 or vehicle for 14 days, were stimulated with TGFβ 5 ng/ml after starvation. Smooth muscle alpha 2 actin (ACTA2) gene expression was measured by RT-qPCR. Efficiency of DOT1L-inhibition was analysed with Western Blot for dimethylated H3K79. Picrosirius Red staining measured collagen I and III deposition. Proliferation was analysed with 5-Bromo-2'-deoxy-uridine (BrdU) labelling. 7–9 week old Col1a2; Cre-ERT 2 ; DOT1l fl/fl mice were injected intraperitoneally with tamoxifen (1 mg/day, 5 days) to induce a fibroblast-specific DOT1L knockout. Bleomycin (0.1 mg) or vehicle was injected subcutaneously (5 days/week, 4 weeks). Injected skin was analysed by OH-prolin assay for collagen content, and by histology for dermal thickness measurement. Results: The DOT1L-inhibitor EPZ-5676 reduced H3K79 dimethylation in all samples. TGFβ increased expression of ACTA2 but 3 out of 4 DOT1L inhibited samples showed a significantly reduced effect of TGFβ on ACTA2 expression. The amount of collagen I and III in the extracellular matrix after 72 hours of TGFβ, was comparable between control and EPZ treated fibroblasts. BrdU labelling assay showed increased proliferation with DOT1L inhibition. In vivo, subcutaneous bleomycin induced an increased dermal thickness and skin collagen content in mice. No difference in the effect of bleomycin was found between mice with a conditional fibroblast-specific DOT1L knockout or wild type mice. Conclusions: In an in vitro model of fibrosis, primary human dermal fibroblasts treated with a DOT1L-inhibitor showed increased proliferation and reduced upregulation of ACTA2 but did not result in detectable differences in collagen deposition. In an in vivo murine model of skin fibrosis, no difference in bleomycin-induced skin thickness and collagen content was found when DOT1L was knocked out in fibroblasts. Disclosure of interest: None declared